2014
DOI: 10.1021/ie402743u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dysprosium-Doped ZnO Nanoparticles for Photocatalysis of a Textile Dye under Visible Light Irradiation

Abstract: Dy-doped ZnO nanoparticles were synthesized with a sonochemical method. X-ray diffraction, inductively coupled plasma, Fourier transform infrared spectroscopy, UV−vis diffuse reflectance spectroscopy, and scanning electron microscopy analyses confirmed the successfully synthesis and nanometric diameter of the samples. Dy-doped ZnO nanoparticles were used for photocatalytic decolorization of C. I. Acid Red 17 solution under visible light irradiation. Among different amounts of dopant agent, 3% Dy-doped ZnO nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(69 citation statements)
references
References 53 publications
4
65
0
Order By: Relevance
“…10B and Table 6). It has been confirmed that the addition of a precise amount of doping element can be critical for achieving high photocatalytic activity as reported in a large number of publications [67]. These results suggest that there exists an optimum dopant concentration of Tb 3+ in the ZrO 2 lattice, which results in efficient separation of charge carriers.…”
Section: Decolorization Studies Of Cr Dye Under Uv/solar Lightsupporting
confidence: 58%
“…10B and Table 6). It has been confirmed that the addition of a precise amount of doping element can be critical for achieving high photocatalytic activity as reported in a large number of publications [67]. These results suggest that there exists an optimum dopant concentration of Tb 3+ in the ZrO 2 lattice, which results in efficient separation of charge carriers.…”
Section: Decolorization Studies Of Cr Dye Under Uv/solar Lightsupporting
confidence: 58%
“…39 The transitions of 4f electrons of lanthanides lead to the implementation of the optical adsorption of catalysts and support the separation of photogenerated electron-hole pairs. In the case of dysprosium dopant, it can exist as Dy 3+ 27 The mechanism of electron capture and transfer is displayed in Scheme 1. The decreased PL intensity in Dy 2 WO 6 -ZnO, reveals that the recombination of electron is suppressed by Dy 2 WO 6 particles, indicating that an appropriate amount of Dy 2 WO 6 could signicantly reduce the irradiative recombination rate of photogenerated electrons and holes in ZnO.…”
Section: Mechanism For Dye Degradationmentioning
confidence: 99%
“…[17][18][19][20][21][22] Nowadays research is focussed on doping of ZnO with rare earth metals and their oxides for the enhancement of photocatalytic activity of ZnO. [23][24][25][26][27] In this connection here we introduced a rare earth metal tungstate, Dy 2 WO 6 , doped ZnO nanoparticles, synthesised by simple hydrothermal method and analysed its photocatalytic activity under natural sun light irradiation in the degradation of two azo dyes (Rhodamine-B and Trypan Blue).…”
Section: Introductionmentioning
confidence: 99%
“…With increasing the initial DO39 concentration from 1 to 23 mg L −1 , the degradation efficiency increases, while the initial DO39 concentration was higher than 23 mg L −1 , %DE decreased. This can be attributed to the shielding effect of the dye molecules at higher concentrations, which resulted in less photon absorption by RGO@Cu 2 O@Cu catalyst [41]. Figure 9b shows the degradation efficiency as a function of the initial pH and process time (the initial DO39 concentration was kept constant at 25 mg L −1 ).…”
Section: Analysis Of Contour and Response Surface Plotsmentioning
confidence: 99%